ANALISIS PERBANDINGAN MUTU BETON fc’25 MPa DAN fc’30 MPa PADA STRUKTUR RUSUNAWA UIGM MENGGUNAKAN SAP 2000 - Elsa Dwi Apriyanti; Indra Syahrul Fuad; Ani Firda; Irwandra Septiadi (LATERAL: Jurnal Teknik Sipil, 2026)
Infrastructure development in the education sector plays an important role. Universitas Indo Global Mandiri supports educational infrastructure development through the provision of student rental flats (Rusunawa). One of the key aspects in rusunawa construction is the structural quality, which must be capable of resisting loads and ensuring occupant safety. Concrete, as the primary structural material, significantly influences the performance of the structure. This study aims to compare the structural design of the Universitas Indo Global Mandiri rusunawa using concrete compressive strengths of fc′ 25 MPa and fc′ 30 MPa, and to determine the differences in internal forces and reinforcement requirements. The building was designed using a Special Moment Resisting Frame (SMRF) system subjected to dead, live, wind, and earthquake loads. Structural analysis was conducted using SAP2000 to obtain internal forces, while Microsoft Excel was used to determine reinforcement requirements. The results showed that beams and columns with fc′ 25 MPa concrete produced lower internal forces than those with fc′ 30 MPa concrete. However, the variation in concrete compressive strength did not affect the required reinforcement. The main beams required 3D16 support reinforcement and 2P10–190 shear reinforcement, secondary beams required 2D16 support reinforcement and 2P10–190 shear reinforcement, while columns required 3D13 longitudinal reinforcement and D10–200 transverse reinforcement.